ANALISIS PERBAIKAN KUALITAS PRODUK HOUSING BOTTOM PADA PT ABC - Simanjuntak, Merlin; Nofriani Fajrah (Computer Science and Industrial Engineering, 2024)
In the midst of the current manufacturing industry competition, companies are required to maintain the quality of their produced products. PT ABC is one of the manufacturing companies engaged in the production of electronic and medical products. In this study, issues were identified in the molding department, which had a high number of black dot defects in Housing Bottom products. The objective of this research is to determine the factors causing the decline in the quality of Housing Bottom products and to identify improvement efforts for the black dot defects. This study uses a fishbone diagram to analyze the factors causing black dot defects and the DMAIC method to determine improvement efforts for the causes of black dot defects. The research findings using the fishbone diagram identified that the cause of black dot defects is a machine factor related to nozzle temperature. Therefore, the improvement efforts conducted using Design of Experiment involve setting the nozzle temperature at 290°C and the metering section temperature at 290°C, resulting in low black dot defects.